Asessing Teacher’s Perception in the Use of Pre-Reading Activities in EFL Classroom - Karolis Anaktototy; Mathilda Huwae (Makassar State University, 2020)
This study was aimed at finding out kinds of pre-reading activities commonly used, and teachers’ perceptions on the use of pre-reading activities. Survey method was used as research method. To collect data, questionnaire and observation checklist were used as research instruments. There were 33 English teachers from 11 Junior High Schools as participants. The result of the study revealed that pre-reading activities were used by English teachers to engage students in reading activities. Pre-reading activities such as asking questions, identifying text structure, previewing, showing picture, brainstorming, and making prediction were the preferable activities applied by teachers. The teachers believed that the use of pre-reading activities in teaching reading is an effective way to improve students’ reading comprehension.